The aging brain : functional adaptation across adulthood - Samanez-Larkin, Gregory R. (American Psychological Association, 2019)
"Brain aging has long been seen as a process of deterioration and decline. Today, this view been challenged with research showing that not all cognitive processes decline with age, that some improve over the course of adulthood, and those that improve can often compensate for those that decline. Chapters in this multidisciplinary volume examine the neural mechanisms underlying changes in the aging brain, changes in learning and memory, risk and protective factors, and the assessment and prevention of cognitive decline"--Provided by publisher.